Prognostic value of cardiac iodine-123 metaiodobenzylguanidine imaging in patients with indications for cardiac resynchronization therapy - Maneikienė, Vytė Valerija; Vajauskas, Donatas; Aidietis, Audrius; Tamošiūnas, Algirdas Edvardas; Ručinskas, Kęstutis; Skiauterytė, Eglė; Marinskis, Germanas (Acta medica Lituanica, 2014)
Background. The aim of our study was to assess the cardiac 123I-MIBG imaging predictive value on the clinical outcome in HF patients with wide QRS complexes and compare its power in different treatment groups. Materials and methods. We have prospectively investigated 67 heart failure patients with the New York Heart Association (NYHA) functional class II–IV, wide QRS complexes (>120 milliseconds), reduced left ventricular ejection fraction (LV EF) eligible for CRT. 123I-MIBG planar and single photon emission computed tomography (SPECT) scans were performed in a supine position with calculation of early and late heart-to-mediastinum (H/M) ratios, washout ratio (WR), summed defect scores and scores difference from SPECT acquisition. All patients were then divided in two groups according to their clinical status – 36 patients underwent implantation of CRT, and 31 patients were continued with OMT. Initial conventional heart failure markers and NYHA were assessed at the time of 123I-MIBG imaging and 6 months later. Comparisons of two groups were done applying the Student’s t-test, and if samples were small, the Fisher’s exact test was used. NYHA groups were compared applying the ANOVA single factor analysis. ROC curve analysis was performed to establish cut off values for predictors of response. Results. Cardiac 123I-MIBG imaging data differed insignificantly, presenting a similar cardiac adrenergic innervation status in both groups. In the CRT group, NYHA and LV EF indicated more pronounced signs of HF. For all patients, NYHA IV patients had significantly larger LV diameter, smaller EF, larger BNP levels, lower late H/M values and larger denervation score difference. Responders to therapy (both groups) had significantly higher early H/M ratio  –  2.35  ±  0.41 than non-responders  –  2.00  ±  0.44 (p  =  0.004), and late H/M ratio  –  2.11  ±  0.44 for responders and 1.72 ± 0.54 for non-responders (p = 0.005). There were no significant differences in regional cardiac 123I-MIBG data for responders and non-responders. Conclusions. Cardiac 123I-MIBG imaging has valuable prognostic power predicting clinical outcomes of HF patients with wide QRS complexes, despite the chosen type of treatment, with better outcomes for patients with early H/M ratio 2.00 and late H/M ratio above 1.77.
Keywords: heart failure; cardiac resynchronisation; nuclear imaging; MIBG